Mientras tanto - Makilan, Marielle delos Reyes 1999
Mientras tanto is a queer folk narrative following a defeated, nine-year-old Sol, in her pursuit of companionship after experiencing heavy bullying because of her nonconformity. When she almost gives up after the whole summer trying and failing to find new friends, she meets Talonon, a forest spirit, on her tenth birthday, who she would instantly connect and spend the remaining days of the summer with, aiding her recovery and healing.